OTONOMI DAERAH DAN KORUPSI - SBM, Nugroho (Jurnal Desentralisasi, 2012)
Arise among scholars about whether the pros and cons of fiscal decentralization to reduce corruption or whether it exacerbates corruption. Facts in Indonesia show that the fiscal decentralization or regional autonomy would exacerbate corruption because there is no public control, there is no state institution that is able to effectively control the local government, and the failure of legislative control functions in the local area. It is necessary to revise Law No. 32 of 2004, the  stablishment of the KPK in the local or district area, and reversed burden of proof application.